2020
DOI: 10.1055/a-1111-8892
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the treatment of trigger digits by extracorporal shock wave therapy (ESWT)

Abstract: Background Currently, extracorporal shock wave therapy (ESWT) has been widely used in tendinopathies, including trigger fingers. Purpose The objective of this study was evaluation of effectiveness of ESWT for trigger digits in a short and mid-term follow-up. Patients and methods Thirty-two patients, 28 women and 4 men, in a mean age of 60 years, with a total of 50 affected digits underwent local extracorporal shock wave treatment. Each patient received 3 applications in a weekly interval. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Unlike steroid therapy, ESWT studies have shown that ESWT affects tenocyte regeneration, leading to an improvement in muscle strength. The effectiveness of ESWT compared with that of local steroid injections showed that ESWT had favorable effects on resolution of pain and improvement of grip strength [33,34]. In our study, we identified improvements in grip strength with ESWT, as well as improvement in simulated card-turning and the picking up of small objects.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Unlike steroid therapy, ESWT studies have shown that ESWT affects tenocyte regeneration, leading to an improvement in muscle strength. The effectiveness of ESWT compared with that of local steroid injections showed that ESWT had favorable effects on resolution of pain and improvement of grip strength [33,34]. In our study, we identified improvements in grip strength with ESWT, as well as improvement in simulated card-turning and the picking up of small objects.…”
Section: Discussionmentioning
confidence: 51%
“…These clinical benefits of ESWT were thought to be mediated by stimulation of dermal fibroblasts, neoangiogenesis, and improvement in the parallel organization of collagen fibers within the skin. Similarly, a beneficial effect of ESWT has been reported for the treatment of trigger finger complaints, resulting from enhanced repair and healing of the degenerated tendon [34]. Overall, as pain, pruritus, and decreased function negatively impact the quality of life after a burn, ESWT may have a global effect in improving quality of life after burn injuries [35].…”
Section: Discussionmentioning
confidence: 92%
“…According to the results of the study, ESWT can be an effective therapy for trigger fingers in 2. and 3. The severity grade may be an alternative for a non-invasive method such as steroid injection [28]. Another study found similar results in pain on the effectiveness of ESWT in trigger finger treatment [29].…”
Section: Discussionmentioning
confidence: 85%
“…The pressure was applied to the patient's tender areas at the base of the thumb, and the midpoint of the adductor longus was gradually increased with a pressure of 1kg/cm 2 until the patient was instructed to "stop. " The pressure increased at the first spot at the base of the thumb was found to be sensitive at 0.3kg/cm 2 and mid-point at 2nd spot adductor longus sensitive at 0.8k/cm 2 [11]. A digital ABS hand dynamometer device was used to assess the grip strength of the patient bilaterally to compare the difference in strength (Figs.…”
Section: Intervention and Outcome Measuresmentioning
confidence: 99%